Understanding the challenges facing small and medium enterprises in foodservice industry: a case of Sri Lankan restaurants - H.A.K.N.S., Surangi; P.S., Ekanayake (Management and Entrepreneurship: Trends of Development, 2022)
Small and Medium Enterprises (SME) play an essential role in the Sri Lankan tourism industry, whereas relatively little is known about the restaurant sector and its challenges. This research aims to examine the challenges facing SME restaurants in Sri Lanka. Given the relatively new and unexplored nature of the research problem, a qualitative, specifically multiple case study method was adopted. Twenty-eight respondents, including the restaurant owner, manager, and two customers from each selected case, were purposively approached. In-depth interviews and observations were used to collect data which was then analysed using the thematic analysis for the implication and conclusion. The key challenges highlighted by the study respondents are lack of skilled employees, high labour turnover, stiff competition in the industry, wrong location, increased budget tourists, lack of technical support from the government authorities and no proper waste management system. The study results support the view that the Sri Lankan restaurant sector requires much more governmental and institutional support. Therefore, the government and other supporting agencies of SMEs can use these findings to develop the SME sector for future programs. Furthermore, this study enriches the understanding of challenges on the experience of Sri Lankan entrepreneurs, which is influenced by the industry-specific factors. JEL Classification: M 2.